Mechanisms of Pacific Summer Water variability in the Arctic's Central Canada Basin. Issue 11 (10th November 2014) - Timmermans, M.‐L.; Proshutinsky, A.; Golubeva, E.; Jackson, J. M.; Krishfield, R.; McCall, M.; Platov, G.; Toole, J.; Williams, W.; Kikuchi, T.; Nishino, S.
Abstract Pacific Water flows northward through Bering Strait and penetrates the Arctic Ocean halocline throughout the Canadian Basin sector of the Arctic. In summer, Pacific Summer Water (PSW) is modified by surface buoyancy fluxes and mixing as it crosses the shallow Chukchi Sea before entering the deep ocean. Measurements from Ice‐Tethered Profilers, moorings, and hydrographic surveys between 2003 and 2013 reveal spatial and temporal variability in the PSW component of the halocline in the Central Canada Basin with increasing trends in integrated heat and freshwater content, a consequence of PSW layer thickening as well as layer freshening and warming. It is shown here how properties in the Chukchi Sea in summer control the temperature‐salinity properties of PSW in the interior by subduction at isopycnals that outcrop in the Chukchi Sea. Results of an ocean model, forced by idealized winds, provide support to the mechanism of surface ocean Ekman transport convergence maintaining PSW ventilation of the halocline.